Samba, lugar e identidade: uma análise geográfica de uma escola de samba - Silva, Marcus Vinicius Sant Ana da (2019)
This work intends to perform a geographical study of a cultural and popular movement of Espírito Santo, the parade of samba schools. Here, samba is analyzed in its urban form, with samba schools being a representation of a particular spatial portion. As the object of study, we chose the Grêmio Recreativo Cultural Escola de Samba Unidos de Jucutuquara, an association based in the neighborhood of the same name and which is known in the middle of samba for having among its members the majority of residents of the neighborhood itself. For historical background, we selected the period between 1972 and 1990, which includes the foundation of the Carnival group that originated the samba school until its first title won in the capixaba carnival.